1993
DOI: 10.1111/j.2044-8295.1993.tb02485.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, reaction time and memory: A meta‐analysis

Abstract: Moderate doses of alcohol impair performance on a variety of information processing tasks. Two separate meta-analyses were conducted on the results of (1) reaction time studies, and (2) recognition memory studies, representing 25 and 16 different task conditions, respectively. In both cases, performance with alcohol (either 0.8 or 1.0 ml/kg body weight) was plotted as a function of performance with no alcohol. For reaction time, a linear fit accounted for 99.7 per cent of the variance. The same function applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
2
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 17 publications
5
58
2
1
Order By: Relevance
“…We found no significant difference between our subjects at a BAL of 0 g/kg and at a BAL of 0.57 g/kg. This is consistent with other studies (Maylor et al 1993;Riedel et al 1985). For driving, any change in PVF as a result of alcohol consumption is probably smaller than the change caused by high speed.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We found no significant difference between our subjects at a BAL of 0 g/kg and at a BAL of 0.57 g/kg. This is consistent with other studies (Maylor et al 1993;Riedel et al 1985). For driving, any change in PVF as a result of alcohol consumption is probably smaller than the change caused by high speed.…”
Section: Discussionsupporting
confidence: 83%
“…In this case, alcohol may act on PVF. The effect of alcohol consumption is probably larger if the task is more complex (Maylor & Rabbit 1993). Post et al found that alcohol increases reaction time at a BAL of 0.75 g/ kg but has no effect at a BAL of 0.4 g/ kg.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of research demonstrates that alcohol can have a detrimental effect on memory (e.g., Bisby, Leitz, Morgan, & Curran, 2010;Brown, Brignell, Dhiman, Curran, & Kamboj, 2010;Clifasefi, Takarangi, & Bergman, 2006;Maylor & Rabbitt, 1993;Ray & Bates, 2006;Soraci et al, 2007). For example, in general, alcohol has a negative impact on memory for personally experienced events (Hashtroudi, Parker, DeLisi, Wyatt, & Mutter, 1984).…”
Section: Criminal Case Processingmentioning
confidence: 99%
“…The slope of the regression line fit to all of the data suggests that, regardless of the type of task, the older adults took approximately 1.7 times as long as the young adults to process the same information. 1 Although the use of Brinley plots was pioneered by researchers studying cognitive aging (e.g., Cerella, 1985;Cerella, Poon, & Williams, 1980;, the approach is quite general, as evidenced by recent studies in the areas of cognitive development (e.g., Fry & Hale, 1996;Kail, 1991Kail, , 1993, neuropsychology (e.g., Ferraro, 1996;Kail, 1994Kail, , 1997Myerson, Lawrence, Hale, Jenkins, & Chen, 1998;Nebes & Brady, 1992;White, Myerson, & Hale, 1997), and psychopharmacology(e.g., Maylor & Rabbitt, 1993). Brinley plots may also be applied to the performance of individuals who differ in ability (e.g., Faust et al, 1999;Hale & Jansen, 1994;Zheng, Myerson, & Hale, 2000) as well as to assess the condition of individual patients in whom some brain disorder or damage is suspected (Schatz, Hale, & Myerson, 1998).…”
mentioning
confidence: 99%